Microwave phase contrast imaging of the subsurface using variation in soil moisture level - Wirth, Sebastian G.; Morrow, Ivor L.; Andre, Daniel (IEEE, 2018)
A new microwave subsurface imaging product is described which is evolved via time lapsed microwave measurements, over several days, of the soil subsurface. The technique exploits changes in soil moisture levels that occur naturally due to evaporative and percolation processes. A novel technique is investigated for detecting and discriminating buried targets; it provides a scaled phase weighting procedure to form a cumulative B-scan image of the subsurface. The algorithm is demonstrated on ground penetrating radar measurements acquired in the XBand spectrum over soil where reference targets and other buried artefacts are placed. Early stage experimental results suggest the approach shows promise to provide enhanced subsurface imagery with reduced clutter and noise levels.
Keywords: Soil; Soil measurements; Permittivity; Microwave measurement; Moisture; Landmine detection; Imaging